Pregabalin vs placebo to prevent chronic pain after whiplash injury in at-risk individuals: results of a feasibility study for a large randomised controlled trial. Issue 2 (8th February 2022) - Nikles, Jane; Keijzers, Gerben; Mitchell, Geoffrey; Farrell, Scott F.; Perez, Siegfried; Schug, Stephan; Ware, Robert S.; McLean, Samuel A.; Connelly, Luke B.; Sterling, Michele
Abstract : Supplemental Digital Content is Available in the Text. A future definitive trial of pregabalin for acute WAD may be feasible with protocol modifications. Pregabalin may be more effective than placebo at 3 months for neck pain intensity. Results will inform the design and logistics of a definitive multisite trial. Abstract: There are few effective treatments for acute whiplash-associated disorders (WADs). Early features of central sensitisation predict poor recovery. The effect of pregabalin on central sensitisation might prevent chronic pain after acute whiplash injury. This double blind, placebo-controlled randomised controlled trial examined feasibility and potential effectiveness of pregabalin compared with placebo for people with acute WAD. Twenty-four participants with acute WAD (<48 hours) and at risk of poor recovery (pain ≥5/10) were recruited from hospital emergency departments in Queensland, Australia, and randomly assigned by concealed allocation to either pregabalin (n = 10) or placebo (n = 14). Pregabalin was commenced at 75 mg bd, titrated to 300 mg bd for 4 weeks, and then weaned over 1 week. Participants were assessed at 5 weeks and 3, 6, and 12 months. Feasibility issues included recruitment difficulties and greater attrition in the placebo group. For the primary clinical outcome of neck pain intensity, attrition at 5 weeks was pregabalin: 10% and placebo: 36% and at 12 months was pregabalin: 10% and placebo: 43%. Pregabalin may be more effective than placebo for the primary clinical outcome of neck pain intensity at 3 months (mean difference: −4.0 [95% confidence interval −6.2 to −1.7]) on an 11-point Numerical Rating Scale. Effects were maintained at 6 months but not 12 months. There were no serious adverse events. Minor adverse events were more common in the pregabalin group. A definitive large randomised controlled trial of pregabalin for acute whiplash injury is warranted. Feasibility issues would need to be addressed with modifications to the protocol.